2014
DOI: 10.1051/0004-6361/201323360
|View full text |Cite
|
Sign up to set email alerts
|

Deep optical imaging and spectroscopy of the lens system SDSS J1339+1310

Abstract: We present deep I-band imaging (NOT-ALFOSC) and spectroscopic (GTC-OSIRIS) observations of the gravitational lens system SDSS J1339+1310. This consists of two images of a lensed quasar, A and B, and a lensing galaxy G between the two quasar images. Our observations led to the following main results: (1) We obtained new accurate positions for B and G (relative to A), as well as structure parameters for the light distribution of G. The new position angle for G is separated by ∼50 • from the previously determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…RATCam-IO:O light curves and OSIRIS spectra of SDSS J1339+1310 indicated that this system is likely the main microlensing factory discovered so far (Shalyapin & Goicoechea 2014a;. Thus, data of SDSS J1339+1310 are very promising tools to reveal fine details of the structure of its accretion flow.…”
Section: Quasar Accretion Flowsmentioning
confidence: 91%
See 1 more Smart Citation
“…RATCam-IO:O light curves and OSIRIS spectra of SDSS J1339+1310 indicated that this system is likely the main microlensing factory discovered so far (Shalyapin & Goicoechea 2014a;. Thus, data of SDSS J1339+1310 are very promising tools to reveal fine details of the structure of its accretion flow.…”
Section: Quasar Accretion Flowsmentioning
confidence: 91%
“…Deep I-band imaging (ALFOSC) and spectroscopic (OSIRIS) observations of SDSS J1339+1310 allowed us to reliably reconstruct the mass distribution acting as a strong gravitational lens (Shalyapin & Goicoechea 2014a). Using a singular isothermal ellipsoid (SIE) to model the mass of the main lensing galaxy (e.g.…”
Section: Lensing Mass Distributionsmentioning
confidence: 99%
“…We note that the first time delay we used (47.0 ± 5.5 days) is more inaccurate than the updated delay in Table 1. Additionally, we have taken the ellipticity and position angle of G in the last column of Table 1 of Shalyapin et al 27 as priors on the SIE+γ lens model. The data fit led to an 1σ confidence interval H model 0 = 69 +10 −8 (accuracy of ∼13%; see Table 2 and the black line in Fig.…”
Section: Sdss J1339+1310mentioning
confidence: 99%
“…Inada et al (2009) reported the discovery of a set of doubly imaged gravitationally lensed quasars, which included SDSS Tables 1 and 3−4 are only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/vol/page J1339+1310. The two images (A and B) of this quasar are located at the same redshift, z s = 2.231, while the early-type galaxy G at z l = 0.607 acts as a gravitational lens (Shalyapin & Goicoechea 2014;Goicoechea & Shalyapin 2016). It is also thought that stellar mass objects in G act as gravitational microlenses, strongly affecting image B (Shalyapin & Goicoechea 2014, henceforth Paper I).…”
Section: Introductionmentioning
confidence: 99%